Private and public co-operation in preventing and addressing corporate crime: the case of labour trafficking in the Finnish construction industry - Davies, Jon (Crime, law and social change, 2024)
Numerous corporate and state processes have long underpinned harms related to human trafficking and exploitation. A consequence of these processes has been a growing interest in how public and private sector organisations co-operate to address key challenges, including accountability for alleged exploitation. The purpose of this article is to examine these public-private sector dynamics in the Finnish construction industry, with a particular emphasis on how stakeholders respond to challenges associated with human trafficking, corporate social responsibility (CSR), and the ‘grey economy’. The core argument developed is that despite a strong regulatory framework in Finnish construction, significant aspects of corporate compliance rely on companies’ voluntary efforts, whereby public sector authorities can have competing views of solutions to address trafficking and exploitation. This paper contributes to existing discussions within white-collar and corporate crime on the dynamics of CSR, and how these apply to the broader context of the grey economy.